Dietary supplementation of squalene increases the growth performance of early-weaned piglets by improving gut microbiota, intestinal barrier, and blood antioxidant capacity - Gao, Yang; Ma, Xue; Zhou, Yingqing; Li, Yongqiang; Xiang, Dong (Frontiers in Veterinary Science, 2022)
This study aimed to investigate the effects of dietary squalene (SQ) supplementation on growth performance of early-weaned piglets. Twenty early-weaned piglets were divided into 2 groups randomly named squalene (SQ) and control (CON). CON group was fed basal diet, SQ was fed basal diet +250 mg/kg squalene. The feeding period lasted 21days. The results showed that SQ significantly increased body weight, average daily gain (ADG), average feed intake (ADFI), F/G ratio and significantly decreased diarrhea index (DI). In terms of blood biochemical indicators, SQ significantly increased anti-inflammatory factors (TGF-β, IL-10, IFN-γ), and decreased pro-inflammatory factors (TFN-α, IL-6). At the same time, SQ significantly increased blood antioxidant indexes (SOD, GSH-Px, CAT, T-AOC), and significantly decreased MDA level. Compared with the CON group, the villus height and V/C ratio of jejunum were significantly increased, while the crypt depth was decreased, and the intestinal permeability indexes (DAO, D-Lac, REG-3, FD4) were significantly decreased, the antioxidant properties of the jejunum were also increased. The results of qPCR showed that the addition of SQ could significantly increase the mRNA expression of jejunal tight junction proteins (ZO-1, Occludin, Claudin, GLP-2, IGF-1), the results were consistent with Western Blotting verification. In addition, adding SQ can increase the intestinal beneficial bacteria (Gemmiger), decreased the abundance of harmful bacteria (Alloprevotella, Desulfovibrio, Barnesiella). It was interesting that the fecal microbes, growth performance parameters, intestinal barrier, and blood biochemical indicators were well correlated together. In conclusion, we suppose that SQ supplementation could effectively improve growth performance of early-weaned piglets by improving gut microbiota, intestinal barrier and blood antioxidant capacity.